Role of Conservative Management in the Treatment of Acute Non-Complicated Appendicitis - Fazal-E-Nauman, Inamullah, Muhammad Hassan, Fazal Hussain, Muhammad Attique Sadiq, Khalil Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to assess the efficiency of non-operative management of acute non-complicated appendicitis in terms of cost effectiveness, as well as related morbidity and mortality. Study Design: A prospective observational research. Place and duration: In the Surgical Unit of Islam Medical College and Teaching Hospital Sialkot for one-year duration from January 2021 to December 2021. Methodology: The study included 110 patients with early acute non-complicated appendicitis who were identified by clinical history, physical, and laboratory testing. 110 patients were given intravenous antibiotics for two days, followed by oral antibiotics for seven days. A proforma was used to collect the data. Several morbidities were recognized and tracked in patients. Results: There were 72 men and 38 women, with an average age of 20 years. Right iliac fossa pain, nausea, vomiting, and anorexia were the most frequent symptoms, whereas fever, tachycardia, and rebound tenderness in the right iliac fossa were the most common signs. Patients were randomly assigned to one of two groups. After an uneventful stay of 2 to 4 days. Patients in Group 1 (36.4 percent) who were treated conservatively had no problems and were discharged after a hospital stay of 2 to 4 days. Within four months, 5 patients (12.5%) and three patients (3%) experienced recurrence within six months. They had appendicectomies done in the traditional way. Wound infection was the sole postoperative complication in one patient (5%). Their hospital stay lasted anywhere from three to six days. Two (2.9%) patients with perforated/gangrenous appendix with appendicolith was found in Group-2 patients who had standard appendicectomy. Wound infection occurred in 4 individuals (5.7 percent), pelvic collection in 3 (4.3 percent), and subsequently small intestinal obstruction (adhesive) in two patients (2.8 percent). Their hospital stay lasted anywhere from four to nine days. Conclusion: Patients who were treated conservatively with antibiotics had minor discomfort and required fewer analgesics. Although surgery-related morbidity, death, and costs were averted, the recurrence rate was not insignificant.